Comparative study between omega 3 fatty acid infusion versus octreotide in management of acute pancreatitis - Arockia, Sugandh; Natraj, Sivarajan (International Surgery Journal, 2022)
Background: Acute pancreatitis is one of the commonest diseases. While some use octreotide infusion, some rely only on fluid therapy and symptomatic treatment. Ongoing research has commented about omega (ω) 3 fatty acid (FA) infusions being the future of acute pancreatitis treatment as it is cheap and has lesser side effects. Methods: This prospective comparative study was done in patients with acute pancreatitis. Patients were divided into two groups, with group A receiving ω-3 FA single-dose infusion of 60 ml/hour over 4-5 hours and the other group B were subjected to injection of octreotide 100 mcg IV 8th hourly for 5 days with IV fluids. The groups were compared based on improvement in biochemical markers, BISAP score and hospital stay. Results: 132 patients were divided into 2 groups, on day 3 serum amylase levels in the ω-3 FA group were 268.54±65.84, and the octreotide group was 299.18±94.31 (p value=0.032). Day 3 serum lipase levels in the ω-3 FA group were 137.07±62.19, and the octreotide group was 172.07±72.46 (p value=0.002). Day 3 BISAP score in the ω-3 FA group was 1.21±0.41, and the octreotide group was 1.39±0.49 (p value=0.023). The duration of hospital stay in the ω-3 FA group was 8.03±1.09 days and in the octreotide group was 11.83±1.04 days (p<0.0001). Conclusions: Patients receiving ω-3 FA reported lower amylase-lipase levels along with a lower BISAP score. Hence looking for a cheaper and safer alternative, ω-3 FA infusion could reduce the problem on the patient and hospitalization concomitant expenses.